The Role of TNF-α in Alzheimer’s Disease: A Narrative Review - Domenico Plantone; Matteo Pardini; Delia Righi; Carlo Manco; Barbara Maria Colombo; Nicola De Stefano (Cells, 2023)
This review analyzes the role of TNF-α and its increase in biological fluids in mild cognitive impairment, and Alzheimer’s disease (AD). The potential inhibition of TNF-α with pharmacological strategies paves the way for preventing AD and improving cognitive function in people at risk for dementia. We conducted a narrative review to characterize the evidence in relation to the involvement of TNF-α in AD and its possible therapeutic inhibition. Several studies report that patients with RA and systemic inflammatory diseases treated with TNF-α blocking agents reduce the probability of emerging dementia compared with the general population. Animal model studies also showed interesting results and are discussed. An increasing amount of basic scientific data and clinical studies underscore the importance of inflammatory processes and subsequent glial activation in the pathogenesis of AD. TNF-α targeted therapy is a biologically plausible approach for cognition preservation and further trials are necessary to investigate the potential benefits of therapy in populations at risk of developing AD.